An Anti-Inflammatory Nutrition in the Prevention and Management of Endometriosis: Implications for Physical Performance and Quality of Life - Piechowicz, Agnieszka; Buczkowska, Ewa; Popczyk, Michał; Przybyłowska, Agnieszka; Popczyk, Natalia; Tymchenko, Hanna; Bryksy, Sylwia; Kaźmierczyk, Jakub; Świątecka, Martyna; Jopek, Jakub (Quality in Sport, 2026)
Introduction and purpose of the work. Endometriosis is a chronic, oestrogen-dependent disease with a complex aetiopathogenesis and a multidimensional clinical presentation, characterised by the presence of active endometrioid glands and stromal tissue located outside the uterine cavity. The diagnosis of endometriosis remains challenging and requires a multidisciplinary approach encompassing physical examination, imaging techniques, and, when necessary, laparoscopy. Current approaches to the treatment of endometriosis are generally classified into three principal categories: pharmacological, non-pharmacological, and surgical interventions. Endometriosis is an inflammatory disease; therefore, any factors affecting immune system regulation may influence its onset, symptom severity and progression. This literature review aims to evaluate the influence of dietary factors on the risk of endometriosis development and on the severity and presentation of its clinical symptoms. Materials and methods. A comprehensive literature search was conducted in the Google Scholar data base up to 1995 and PubMed up to data base. The review included clinical control studies, cross-sectional studies, prospective cohort studies, and randomised studies. Summary. Current evidence indicates that diets rich in anti-inflammatory components may substantially reduce the risk of endometriosis and mitigate the severity of associated symptoms. Nevertheless, further research is required to elucidate the specific mechanisms and the extent to which individual dietary components influence the progression of the disease.